THE ROLE OF ELECTROLYTE METABOLISM ON CARDIAC TISSUE - Khidirova Gulnoza Ozodovna; Abdumutalova S. D. (Journals Park Publishing, 2025)
As a highly intricate electrochemical apparatus, the heart functions as an organ that requires specific domiciles of electrolytic to maintain its proper functioning. Calcium (Ca²⁺), phosphorus (P), and potassium (K⁺) play some of the most pivotal roles when it comes to influencing cardiac physiology by regulating contractions alongside several other metabolic processes together with electrical conductivity. An imbalance in these elements can lead to arrhythmias, heart failure, and even myocardial dysfunction. In addition to that, the histological configuration of the heart is equally as important as the myocardium, endocardium, epicardium, and the specific conduction system that enables the heart to contract in a synchronized manner without losing the ability to eminently deliver blood throughout the body. This article examines the impact these electrolytes have on cardiac health and the remarkable histological architecture of the heart that helps support its continuous function. As a muscular organ, the heart does perform a number of vital tasks such including contraction and delivery which depend on and are controlled by optimal electrolyte levels. For cardiovascular health, these electrolytes are essential because they are involved in action potential regulation, muscle contraction, and cellular metabolism. Their role widens to include vascular tone modulation, enzymatic function alteration, and myocardial energy production. The disturbance of these electrolytes can lead to grave medical disorders underlining the necessity of further research into their specific roles and effects on cardiac tissue.
Keywords: Calcium, phosphorus, potassium, arrhythmia, bradycardia, hypokalemia, hyperkalemia, sodium.